Perspektywy, możliwości i ograniczenia badań łączących psychologię i historię nad edukacją i wychowaniem dzieci i młodzieży u progu nowoczesności - Bołdyrew , Aneta; Pająk , Paulina (Studia Edukacyjne, 2021)
The past three decades have seen a heightened interest in integrating psychology and history in educational research. The aim of this article is to present interdisciplinary approaches combining psychological and historical perspectives in research on education and upbringing of children and youth on the eve of modernity. Using the examples of research projects that blend historical methods with Lifespan Developmental Psychology and Social Psychology, the authors analyse their possibilities and limitations. This article brings a new perspective to the studies on childhood and adolescence, with a special focus on people living in the Polish lands at the turn of the twentieth century.